Practical Test-Driven Development using C# 7 : Unleash the power of TDD by implementing real world examples under .NET environment and JavaScript. - Callaway, John (Packt Publishing, 2018)
Test-Driven Development (TDD) is a methodology that helps you to write as little as code as possible to satisfy the software requirements, and that what you've written does what its supposed to do. If you're looking for a practical resource on Test-Driven Development this is the book for you. You've found a practical end to end guide that will ...
The Interface Segregation principle.
Keywords: C.; Microsoft .NET Framework.; Application software -- Development.; Logiciels d'application -- Développement.; Application software -- Development